Relationship of Scores of Empathy with Human Body Dissection and Gender among Undergraduate Medical Students of BPKIHS - Shah, Sandip; Koirala, Sarun; Khanal, Laxman; Baral, Presha (Nepal Journal of Health Sciences, 2022)
Introduction: Medical empathy is defined as the predominantly cognitive attribute that involves the ability to understand patients’ experiences, concerns, and perspectives, and communicate this understanding with the intention of helping.Objectives: The main aim of present study was to determine the relationship of human body dissection and gender with level of empathy among the first and third year undergraduate medical students of B.P. Koirala Institute of Health Sciences.Methods: A cross-sectional study conducted on first and third years medical students between the periods of August 2020 to March 2021. “The Jefferson Scale of Physician Empathy-Student version” was used for assessment of empathy. Sample size of the study was 176 and the results were analyzed in Statistical Package for the Social Sciences, version 11.5. Student’s t-test, ANOVA and bivariate correlation models were employed for statistical analysis. The p